Fiesta moon eaudiobook Moonstruck series, book 2. - Windsor, Linda (Moonstruck, 2015)
Christy finalist Linda Windsor's hilarious and uplifting Moonstruck series proves that higher powers are indeed at work when it comes to matchmaking. For playboy Mark Madison it seems like nothing could be further from the truth his first day on the construction site for a new orphanage in Mexico. A chilly reception from the beautiful social worker Corinne Diaz is the precursor to mayhem and disaster for Mark. But when a terrible curse threatens the completion of the project, the two must band together to find the culprit.